Enhanced piezoelectricity and electromechanical efficiency in semiconducting GaN due to nanoscale porosity. (December 2020) - Calahorra, Yonatan; Spiridon, Bogdan; Wineman, Adina; Busolo, Tommaso; Griffin, Peter; Szewczyk, Piotr K; Zhu, Tongtong; Jing, Qingshen; Oliver, Rachel; Kar-Narayan, Sohini
Highlights: The effect of nanoscale porosity on the piezoelectricity of GaN is investigated. Piezoelectric force microscopy shows porous 40% porous GaN having 2–3 times higher piezoelectric coefficient than bulk GaN . Finite element simulations suggest that increased mechanical compliance due to porosity gives rise to the observed enhanced piezoelectricity in GaN. Simulations also show that the stress-based figure of merit is increased 10 fold from bulk to 40 vol% porous GaN. Abstract: Electrical polarization phenomena in GaN are important as they have significant impact on the operation of modern day energy efficient lighting and are fundamental to GaN-based high power and high frequency electronics. Controlling polarization is beneficial for the optimization of these applications. GaN is also piezoelectric, and therefore mechanical stress and strain are possible handles to control its polarization. Nonetheless, polar semiconductors in general, and GaN in particular, are weak piezoelectric materials when compared to ceramics, and are therefore not considered for characteristic electromechanical applications such as sensing, actuation and mechanical energy harvesting. Here, we examine the effect of nanoscale porosity on the piezoelectricity of initially conductive GaN. We find that for 40% porosity, the previously conductive GaN layer becomes depleted, and exhibits enhanced piezoelectricity as measured using piezoresponse force microscopy, as well as by using a mechanical energy harvesting setup. The effective piezoelectric charge coefficient of the porous GaN, d 33, eff, is found to be about 8 pm/V which is 2-3 times larger than bulk GaN. A macroscale device comprising a porous GaN layer delivered 100 nW/cm 2 across a resistive load under a 150 kPa mechanical excitation. We performed finite element simulations to analyze the evolution of the piezoelectric properties with porosity. The simulations suggest that increased mechanical compliance due to porosity gives rise to the observed enhanced piezoelectricity in GaN. Furthermore, the simulations show that for stress-based excitations, the porous GaN electromechanical figure of merit is increased by an order of magnitude and becomes comparable to that of barium titanate piezoceramics. In addition, considering the central role played by GaN in modern electronics and optoelectronics, our study validates a very promising research direction when considering stress-based electromechanical applications which combine GaN's semiconducting and piezoelectric properties. Graphical abstract: Image, graphical abstract